FARMERS’ PARTICIPATION IN EMPOWERMENT PROGRAMS OF MUHAMMADIYAH COMMUNITY ORGANIZATION IN PASEH DISTRICT - Utan Sahiro Ritonga; Tri Hanifawati (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2021)
All this time empowerment to farmers has been carried out through organizational approaches from the government, academics, and NGOs based on examples of programs that have been successful in advanced regions. Meanwhile, the Muhammadiyah community organization carries out the dawah activities through empowerment programs in one of the underdeveloped villages in the Paseh District. Therefore, it is necessary to know the success level of empowerment programs according to participation level related to the farmers’ background as information for designing the implementation of more successful empowerment programs. The research method of this study based on the classification was quantitative research with a survey approach through non-probability questionnaires collected to 37 farmers that were then analyzed using percentage technique and Pearson’s chi-square. The percentage calculation shows that farmer participation level was in the medium category. Results of Pearson’s chi-square and correlation tests using gamma show that the experience of farmers in partnership has a positive correlation to socialization activities. The involvement of farmers in the community organization has a positive correlation to socialization and training activities. The community organization’s attitudes towards farmers have a positive correlation to coaching activities. The farmers’ age has a negative correlation, while the length of farming, the cultivated land status, the experience of farmers participating in socialization, the experience of farmers participating in training, and community organization’s attitudes for the farmers has a positive correlation to partnership activities in empowerment programs. Muhammadiyah community organization should synergize with the government and other institutions for implementing empowerment programs by reviewing farmers’ backgrounds to reach high participation.